EMPLOYEE FINANCING SYSTEM ANALYSIS WITH MURABAHAH CONTRACTS AT BPRS BAITUR RIDHA BANDUNG - Akhmad Baidun; Syamsu Rijal; Yeti Yeti; Norvadewi Norvadewi; Akhmad Nur Zaroni (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
This research This study was motivated by the products offered by BPRS Baitur Ridha Bandung, specifically employee financing products with murabahah, which have recently received a lot of attention from customers. Employee financing is available to internal and general employees of BPRS Baitur Ridha Bandung for personal use. This study is a field study. Data sources include primary and secondary data gathered through observations, interviews and documentation. After collecting the data, the writer analyzes it using qualitative descriptive methods with descriptive, inductive and deductive methods. The findings show that the employee financing system with murabahah in BPRS Baitur Ridha Bandung is primarily in accordance with Islamic economics. It has a significant positive impact and influence. Similarly, elements of irregularities according to the Islamic economic system have yet to be discovered in the implementation. Keywords: ;;